A ESTÉTICA DO TURBILHÃO: UM ASPECTO DO MODO DE NARRAR DE ALCIENE RIBEIRO - Amanda Eliane Lamonica Araujo (2024)
Alciene Ribeiro, a contemporary author and writer, by utilizing the plasticity of the constant "coming-and-going" in the manipulation of various elements of the narrative, generates what is called in this work the "whirlwind aesthetic." Thus, this research aims to demonstrate this aesthetic to the reader through the author's peculiar way of narrating in the works Filho de Pinguço (Ribeiro, 1992), O Mágico de Olho Verde (Ribeiro, 1984), and the short story “Pensar Axilas” from the book Mulher Explícita (Ribeiro, 2019). The present study on the "whirlwind" in Alciene Ribeiro's narratives significantly contributes to the understanding of contemporary literary technique and offers insights into the fragmentation of narrative elements, highlighting the importance of looking beyond the surface to truly grasp the depth and richness of life and the narratives constructed by Alciene Ribeiro. For this research, theoretical contributions on narrative elements were used, including Candido (2000), Cortázar (2008), Coelho (2002), Duarte (2010), Genette (1972; 1995), Leite (2007), Moisés (2004), Pereira (2018), Reis and Lopes (1989), and Todorov (1971), as well as theories of the short story. The structure of this work is organized into seven sections: introduction, critical review, theory for the analyses, Filho de Pinguço, O Mágico de Olho Verde, “Pensar Axilas,” and the final considerations. To demonstrate the "whirlwind," the analyses of the works follow the path of description-analysis-interpretation, focusing on: plot, narrator, character, chronotope, metaphors, and final analysis. Keywords: Literary analysis. Narrative constructicon. Tourbillon aesthetics Alciene Ribeiro.